Strategiczna rachunkowość zarządcza. Pojęcie, cele, narzędzia - Nowak, Marta; Nowak, Edward (Strategic Management Accounting. Concept, Goals and Instruments, 2006)
The paper treats of the problems of strategic management accounting. The various stakeholders groups creating strategy of a business entity are presented. The owner's strategy is shown as a superior strategy. On this background both problems of management accounting in management process and the definition of strategic management accounting have been formulated. Different instruments of strategic management accounting have been presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (4); 2006; nr 1119, s. 29-35